Efficacy and safety of R-GEMOX in relapsed or refractory diffuse large B-cell lymphoma: A single-center experience in Vietnam - Duyen, Dinh Thi Hai; Huyen, Tran Thi; Lan, Nguyen Thi Mai (Tạp chí Nghiên cứu Y học, 2025)
Diffuse large B-cell lymphoma (DLBCL) is the most common histologic subtype of non-Hodgkin lymphoma (NHL), yet a substantial proportion of patients experience relapse or refractory disease following initial therapy. Among various salvage regimens, R-GEMOX - comprising rituximab, gemcitabine, and oxaliplatin - has shown promising efficacy and a tolerable safety profile. This retrospective cohort study aimed to evaluate the treatment outcomes and adverse events associated with R-GEMOX in patients with relapsed or refractory CD20-positive DLBCL treated at Hanoi Oncology Hospital. A total of 39 patients who received at least four cycles of R-GEMOX between January 2018 and May 2024 were included. Treatment response was assessed using the Lugano 2014 criteria, and toxicities were graded per CTCAE v4.0. The median age of the cohort was 57.2 years old. The overall response rate (ORR) was 69.2%, including a complete response rate of 28.2% and a partial response rate of 41.0%. Stable disease and progressive disease were observed in 7.7% and 23.1% of patients, respectively. Grade 3-4 hematologic toxicities occurred in 30.8% of cases. Median progression-free survival (PFS) was 9.5 months, while median overall survival (OS) reached 15.7 months. These findings suggest that R-GEMOX is an effective and tolerable salvage regimen in the management of relapsed/refractory DLBCL, particularly for patients ineligible for high-dose chemotherapy or stem cell transplantation.